2017
DOI: 10.1007/s11205-017-1817-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Disadvantages: Prevalence and Categories of Old-Age Social Exclusion in Belgium

Abstract: Research involving Human Participants and/or Animals: not applicable Informed consent: not applicable AcknowledgmentsWe would like to acknowledge the four anonymous reviewers for the valuable suggestions on this article. We acknowledge the provincial and local governments of the participating municipalities for their support and cooperation throughout the research. We thank the older volunteers for their commitment throughout the research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Local governments also provide financial and care assistance to the oldest old in China, which could reduce their risk of exclusion from social relationships (Phillips & Feng, ). However, age‐related mobility and other problems may be barriers for older people at advanced age, preventing their participation in social activities, a finding consistent with research in Belgium (Van Regenmortel et al., ). Combined with ageism, they could be more likely to feel isolated from others.…”
Section: Discussionsupporting
confidence: 84%
“…Local governments also provide financial and care assistance to the oldest old in China, which could reduce their risk of exclusion from social relationships (Phillips & Feng, ). However, age‐related mobility and other problems may be barriers for older people at advanced age, preventing their participation in social activities, a finding consistent with research in Belgium (Van Regenmortel et al., ). Combined with ageism, they could be more likely to feel isolated from others.…”
Section: Discussionsupporting
confidence: 84%
“…Victor et al ., 2009; Cramm et al ., 2018) and the strength of the multi-dimensional framework of social exclusion. Broad approaches to the research of exclusion can also accommodate the study of accumulation of exclusion across different dimensions and over time (Becker and Boreham, 2009; Heap et al ., 2017; Van Regenmortel et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the reasons why we do not know what encourages social participation amongst older people, and what the obstacles are to their engagement in social life. Research on old-age social exclusion has demonstrated that social participation is one of the main and most frequent domains included in different schemes of social exclusion (Van Regenmortel et al, 2016;Van Regenmortel et al, 2018;Vrooman and Hoff, 2013;Walsh et al, 2017). Usually, such research does not, however, provide details about the kinds of activities that older people are involved in (Galenkamp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%